Pengaruh Lingkungan Kerja Fisik Terhadap Produktivitas Kerja Karyawan Bagian Produksi Pada PT Vista Agung Kencana - Dzahabiyyah, Salwa; Wita Farla; Karimudin, Yos (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to test or analyze how the influence of the physical work environment on the work productivity of production employees at PT Vista Agung Kencana. The population in this study were all employees of the production division of PT Vista Agung Kencana, Muara Enim Regency, totaling 150 employees. The sampling technique of this study used a purposive sampling technique. thus the respondents of this study were as many as 40 respondents from all permanent production employees at PT Vista Agung Kencana. This study used primary data obtained through questionnaires and simple linear regression analysis as a data analysis technique. The data was processed using the Statistical for Product and Service Solution (SPSS) program release 26. The results showed that the physical work environment had a positive and significant effect on the work productivity variable for employees in the production department at PT Vista Agung Kencana.